Problems and prospects of development of the tourist and recreationalspheres in the former Soviet Union - V. N. Pishchulin (Проблемы постсоветского пространства, 2017)
The relevance of the chosen subject is caused by the social and economic changes taking place in life of society in the former Soviet Un- ion. Nowadays the tourist and recrea- tional sphere became the important di- rection of development of economy of our country. Its development is of great importance for transition to modern and innovative economic type of develop- ment of Russia. The article assesses the tourism potential of the Lipetsk region, highlights the main tourist clusters, con- siders the problems and prospects of development of tourism in the region.